SURVEY PERBANDINGAN MINAT MASYARAKAT MELAKUKAN VAKSINASI COVID-19 BEDASARKAN JENIS VAKSIN DI KOTA TERNATE - Soesanti, Soesanti; Husen, Abd Hakim (NHM PRESS, 2023)
The Covid-19 pandemic that is currently hitting the world has caused high morbidity and mortality throughout the world. The World Health Organization (WHO) has declared Covid-19 a Global Pandemic so that mitigation efforts must be carried out in accordance with statutory provisions. The vaccination program provided by the Indonesian government aims to tackle the Covid-19 pandemic. The results of several surveys show that there are still many Indonesians who refuse to be vaccinated against Covid-19. Vaccination is the most effective and efficient public health effort in preventing several dangerous infectious diseases. Even so, it cannot be denied that there are still many groups of people who refuse vaccination due to a lack of public knowledge regarding the Covid-19 vaccine. Vaccination is expected to be accessible, timely and fair, and to reach targets who need it most, including marginalized communities. Marginalized populations that are often hard to reach are vulnerable to frequent supply-related barriers to vaccination. Some related barriers are barriers related to geography, temporary displacement due to nomadic lifestyles, discrimination by some health care providers, inadequate or lack of inclusive vaccination systems and insecurity due to war and conflict. This research aims to determine the characteristics of the Comparative Survey of Community Interest in Carrying out Covid-19 Vaccination Based on Vaccine Type in Ternate City. This research is a descriptive research. Data analysis was carried out using the SPSS 23 application. The sample in this study was used, namely that the sample was taken based on certain characteristics and criteria.